Self-efficacy assessment hinders improvement on a deliberate cricket bowling practice task - Raman, Dhruv; Rajaraman, Bittu (Frontiers in Psychology, 2023)
Previous research indicates that external focused attention is linked to superior performance on motor tasks. This study examined how attention directed towards one's self-efficacy affected performance in a cricket bowling task. In the pre-test phase, participants attempted to bowl in a designated "good length" zone across twelve trials. Following this, participants were randomly assigned to either an experimental group, where they rated their own general and task-specific self-efficacy, or a control group, where they rated someone else's ability. They each then bowled twelve more trials. Their performance was measured based on the number of trials that were bowled within the standard "good length" zone. Paired t-tests showed that while the performance of the control group improved significantly from pre-test to post-test, t = 2.613, p = 0.008; the experimental group did not show a significant improvement, t = 1.156, p = 0.131. Results indicate that asking people to rate their self-efficacy level may reduce their improvement on a deliberate practice task. Implications for sport performance and researchers are discussed.